Mediating effect assessment of ifosfamide on limb salvage rate in osteosarcoma: A study from a single center in China - Li, Yan; Fu, Yiwei; Zhang, Zhaohui; Wang, Zhuo; Yin, Junqiang; Shen, Jingnan (Frontiers in Oncology, 2022)
Osteosarcoma is one of the most prevalent primary bone malignancies in children and adolescents. Surgery and chemotherapy are the standard treatment methods of osteosarcoma. Methotrexate, adriamycin, and cisplatin, and methotrexate, adriamycin, cisplatin, and ifosfamide regimens are both first-line neoadjuvant chemotherapy regimens for osteosarcoma. Moreover, the use of ifosfamide is highly controversial. Most studies of ifosfamide focused on the overall survival rate and event-free survival rate; few studies concentrated on surgical options. We conducted this retrospective study to compare the baseline characteristic of amputation and limb salvage osteosarcoma patients. Furthermore, we analyzed the direct and indirect roles in surgical decision-making and found that ifosfamide may play a partial mediating role in the surgery option choice by mediating tumor mass volume change, tumor response, and the shortest distance from the center of main blood vessels to the margin of the tumor lesion.